Use the protected arrangement method to resolve the assignment problem of the fuzzy triangular number in the industrial sector in Baghdad - Maytham Mowaffak Shaker; Zena Hekmat Fakhri; Khalid Zgiton Chalobe (Journal of Madenat Alelem University College, 2014)
Assignment problem is considered a well-known topic and used often in solving real problems in the areas of economic, administrative and engineering, as looking at how to distribute a certain number of resources, workers, machines ... , For a certain number of activities in an efficient manner, so as to achieve less expensive or better performance as a result of the completion of these tasks. This cost is usually deterministic in nature, while fuzzy triangular number was taken which denoted the realistic and more of a general nature in our daily lives.In order to get the best solution was to convert the fuzzy state in to the linear programming model and solved using Hungarian Methodto get the results.